Analise ‘in vitro’ do efeito do agente silano em uma resina laboratorial de segunda geração na resistência adesiva ao do substrato dentinário utilizando dois sistemas de cimentos resinosos, por meio do teste de micro-tração - Grullón, Patrícia Grau (2005)
The aim of this investigation was to analyze the bond strength between a Second Generation Laboratorial Resin and dentin structure, verifying the effect of the internal treatment with silano agent, using two resin cement systems. The oclusal surface of twenty third human molars was removed and later polished. Blocks were constructed using the Second Generation Laboratorial Resin GradiaTM directly on the dentin structure. The 4 evaluated groups were: I) chemical resin cement sandblasting/silano; II) chemical resin cement sandblasting; III) dual resin cement sandblastings/silano/ and IV) dual resin cement sandblasting. Bonded sticks (0.9 mm² ± 0.2 mm²) were gotten by means of parallel and perpendicular cuts in the bonding interface. Each stick was fixed by its extremities to the modified device for the micro-tensile test in order to locate the area of adhesion perpendicular to the long axle of the force, in the universal assay machine (EMIC) crosshead speed 1mm/min. The final values of bond strength were express in MPa. The fracture modes were analyzed under 40X magnification. The data were submitted to two-way ANOVA and Tukey´s test (α=0.05). Results: The average values in MPa presented by each group were: I) 19.10±2.88; II) 13.67±3.31, III) 11.95±3.96; IV) 25.14±5.66. The analysis two-way ANOVA showed that the factor Treatment was significant (p=0.05), as well as the interaction of the factors Treatment and Type of cement (p=0.0001). The factor Type of cement was not significant (p=0.25). Conclusion: They were not statistical differences between the bond strength of the two resin cements, the internal treatment was significant, for the dual cement the application of the silano agent lowed the values of bond strength in the chemical cement the application of the silano increased the values of adhesive resistance, being not significant. The fracture modes were predominantly adhesive between the Second Generation Laboratorial Resin of and the resin cement.